Antibiofilm activity from novel soil bacterial species of Paenibacillus Haemolyticus strain 139si towards new therapeutic management of chronic and recurrent tonsillitis / Saad Musbah Naji Alasil - Saad Musbah, Naji Alasil (2013)

(untitled)
A biofilm is a layer of microbial cells that is firmly attached to surfaces and enclosed in a matrix of polysaccharide material. Biofilms pose a problem to the environment, industry and the medical field causing a variety of chronic infections particularly in the ear, nose and throat like chronic and recurrent tonsillitis. Therefore, development of new therapeutic strategies against biofilm-forming pathogens is essential in the management of biofilm-associated tonsillar diseases. One hundred and forty (140) palatine tonsils were collected from 70 patients undergoing tonsillectomy at University Malaya Medical Centre (UMMC) and the type of microorganisms and their antimicrobial susceptibility of both swab and biopsy tonsillar specimens were identified. The presence of bacterial biofilms in the excised tonsils was detected via Scanning Electron Microscopy and Confocal Laser Scanning Microscopy, and the ability of tonsillar bacterial isolates to form biofilms was determined via Congo Red Agar method and Microtiter Plate assay. A culture filtrate from novel soil bacterial species of Paenibacillus haemolyticus strain 139SI was tested for its acute toxicity in rats and evaluated for its antibiofilm activity both in vitro via Microtiter Plate assay and in vivo using a rat model of chronic lung infection. The soil bacterial filtrate was purified via High Performance Liquid Chromatography, and the selected compounds were tested against clinical isolates for their antibiofilm activity. The most potential antibiofilm compounds were further analysed via Liquid Chromatography-Mass Spectrometry. Two main groups of clinical cases were classified as infected tonsils represented by 49 (70%) cases of recurrent tonsillitis, 9 (12.85%) cases of chronic tonsillitis in addition to non-infected (hypertrophied) tonsils represented by 12 (17.14%) cases of obstructive sleep apnea. The presence of bacterial biofilms was detected in 42 (60%) patients. iii A total number of 464 bacterial isolates were recovered from tonsillar specimens with 184 (39.65%) Staphylococcus aureus isolates as the most common followed by 86 (18.53%) of Haemophilus influenzae isolates. Three susceptibility patterns were found among S. aureus isolates with 89.4% being susceptible to all tested antimicrobial agents, 10.6% resistant to fusidic acid and 0.5% resistant to both methicillin and fusidic acid. The antimicrobial agent co-trimoxazole showed the highest rate of resistance among all bacterial isolates including 55 (98.2%) isolates of Group B Streptococci and 11 (78.5%) isolates of Group A Beta-Haemolytic Streptococci, 14 (56%) isolates of Group G Streptococci, 10 (32.2%) isolates of Haemophilus pararinfluenzae and 27 (31.3%) isolates of Haemophilus influenzae. The soil bacterial filtrate of Paenibacillus haemolyticus strain 139SI showed no signs of toxicity and a significant antibiofilm activity was detected in the lungs of chronically-infected rats. Four potential antibiofilm compounds of the bacterial filtrate namely FR4, FR5, FR8 and FR13 were identified. The compound FR5 with a molecular weight of 253.237 and a molecular formula of C8H20N3O4P exhibited the strongest antibiofilm activity. In conclusion, discovery of an antibiofilm activity from a novel soil bacterial species of Paenibacillus haemolyticus strain 139SI adds an important dimension in the search for new potent compounds against biofilm infections.